Short-term operating room scheduling: a parallel machine under resource constraints problem. (1st March 2021) - Abdeljaoued, Mohamed Amine; Bahroun, Zied; Saadani, Nour El Houda
The paper tackles the daily scheduling of surgical operations in an operating theatre. The considered operating rooms are identical and the set of operations is subdivided into groups, each of them performed by a single surgeon. The objective is to minimise the ending time of the last completed operation (makespan). The problem is NP-hard and is part of the parallel machine scheduling under resource constraints. We provide two mathematical models and compare their performance. The first is based on parallel machines scheduling, while the second highlights the similarities with the strip packing problem. Two heuristics based on a dichotomic approach are then introduced. An experimental study comparing their results to optimal solutions, lower bounds and an existing heuristic from the literature shows that the second proposed method performs the best and provides near-optimal or good results for realistic-size instances in reasonable computational times.